The man from U.N.C.L.E. The complete season 1 [videorecording (DVD)] - Rolfe, Sam H., 1924-1993; Felton, Norman, 1913- (Warner Home Video, 2015)
Working for the United Network Command for Law and Enforcement, the dapper, suave Napoleon Solo, and the equally dashing Illya Kuryakin, jet to exotic locations, defending the world from evil and chaos in this hit spoof on the espionage genre.